Progress and challenges of detecting biomarkers for the development of pesticide biosensor in rice plants - Ma, Nyuk Ling; Nisrin, Abd Kadir; Mohammad Mustaqim, Ahmad Nordin; Tan, Suat Hian; Lam, Su Shiung (Elsevier, 2018)
Pesticides are widely used in agriculture to increase crop productivity. This results in the transfer of pesticide residues to the consumable products made from crops and could be harmful when ingested. While the toxicogenomic effects of pesticides have been widely studied on living organism exposed to pesticide, limited information is available on the biomarkers synthesized in plant cells resulting from pesticide exposure. The direct detection of these biomarkers is potentially beneficial as a tool to the detection of foods contaminated with pesticides and could, therefore, provide useful dietary protection and guidelines to the consumer. This chapter begins with a review on the various types and effects of pesticides used in rice fields, which is then followed by an extensive review on the use of different “omics” approaches for the detection of pesticide biomarkers along with the associated challenges and breakthroughs.